Development of Animation Video Media (VA) Themes of National Events in the Colomination Period Class V Elementary School - Nurul Ikhsan Saputra; Novanita Whindi AR (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
This study aims to (1) describe the design of learning animation videos, (2) describe the results of the validity of the development of learning animation videos, and (3) determine the effectiveness of the developed learning animation videos. The development model used is the Bord and Gall model. The data in this study were collected by interview and test methods. The instruments used in collecting data are interviews and objective tests. The results of the research are as follows. (1) Design an animated video made in a video script. This manuscript was turned into an animated video through the development stages of Bord and Gall. (2) The results of the validation of the animated video based on the assessment of media experts, namely 77.33% in the Eligible category, material expert, obtained a percentage of 91.66% with a very decent category, the assessment of education experts, obtained a percentage of 85.71% with a very decent category. Limited media test results obtained 81.78%, with a very feasible category. The results of the field media test obtained a percentage of 94% with a very feasible category. Thus the learning animation video developed is declared valid. (3) The effectiveness of the developed video is 82.89%. There is a significant difference in student learning outcomes between before and after using animated videos. Thus the animated video developed is effective in improving student learning outcomes. This study suggests that teachers use animated videos in learning that are developed in the learning process.